2016
DOI: 10.1007/s10973-016-5933-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of thermal and mechanical properties of a biocomposite based on natural rubber and 45S5 Bioglass® particles

Abstract: Biocomposites based on natural rubber (NR) reinforced with 45S5 BioglassÒ (BG) particles were obtained by casting/evaporation method in which NR was dissolved in chloroform and mixed with BG particles. Structural, mechanical, and thermal tests were performed on the biocomposites to evaluate the influence of BG particles on the properties of the NR matrix. Thermogravimetric tests (TG/DTG) of the biocomposites showed decomposition profiles similar to that of NR, and the main peak of the DTG curve was well define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…The incorporation of TiO 2 nanoparticles into the fibers promoted an increasing trend of the elastic modulus from (9 ± 1) MPa for the PVDF membrane to (11 ± 1) MPa at a concentration of 10% m/v. This behavior was attributed to the increased charge transfer from the matrix to the ceramic nanoparticles 67 . Increasing the TiO 2 content did not promote a significant change in the mean elastic modulus values, which was (9 ± 1) MPa for the pure PVDF membranes and (10 ± 2) MPa at a concentration of 60% m/v.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The incorporation of TiO 2 nanoparticles into the fibers promoted an increasing trend of the elastic modulus from (9 ± 1) MPa for the PVDF membrane to (11 ± 1) MPa at a concentration of 10% m/v. This behavior was attributed to the increased charge transfer from the matrix to the ceramic nanoparticles 67 . Increasing the TiO 2 content did not promote a significant change in the mean elastic modulus values, which was (9 ± 1) MPa for the pure PVDF membranes and (10 ± 2) MPa at a concentration of 60% m/v.…”
Section: Resultsmentioning
confidence: 87%
“…This behavior was attributed to the increased charge transfer from the matrix to the ceramic nanoparticles. 67 Increasing the TiO 2 content did not promote a significant change in the mean elastic modulus values, which was (9 ± 1) MPa for the pure PVDF membranes and (10 ± 2) MPa at a concentration of 60% m/v. Furthermore, the presence of TiO 2 in the membrane facilitated a significant decrease in the ε break value, with an average reduction of 27% for 10% m/v insertion relative to the PVDF membranes.…”
Section: Mechanical Stability Of Membranesmentioning
confidence: 80%
“…The mass loss due to this main event was about 90.3%. Decomposition of non‐rubber components, such as fatty acids, produces a small peak between 150 and 280°C, where 6.5% of the mass was lost 65 . At 600°C the final residue of the neat NR was about 2.2%.…”
Section: Resultsmentioning
confidence: 99%
“…Decomposition of non-rubber components, such as fatty acids, produces a small peak between 150 and 280 C, where 6.5% of the mass was lost. 65 At 600 C the final residue of the neat NR was about 2.2%. As shown in Figure 5b,d, the neat NR corresponds to a small shoulder between 380 and 450 C. It is possible to attribute this shoulder to different degradation temperatures of the other NR constituents.…”
Section: Thermal Analysismentioning
confidence: 97%
“…The thermal and mechanical properties of natural rubber–based biocomposites filled with bioglass particles composed of 24.3% of Na 2 O, 26.9% of CaO, 2.5% of P 2 O 5 , and 46.3% SiO 2 at 90:10, 70:30, and 50:50 natural rubber:bioglass ratios have been investigated by Silva et al The authors have found enhanced thermal stability of the composite due to higher bioglass amounts, as well as improvement in the mechanical properties, what in their opinion demonstrates potential biomedical applications.…”
Section: Introductionmentioning
confidence: 99%